Training on the Use of Chatbots as Information Providers at the Sang Nila Utama Museum Riau Province: Pelatihan Penggunaan Chatbot Sebagai Penyedia Informasi Di Museum Sang Nila Utama Provinsi Riau - Arbi Haza Nasution; Winda Monika; Husnul Kausarian (Universitas Lancang Kuning, 2023)
In the era of society 5.0, memory institutions such as museums and libraries need to implement information technology, starting from digitizing collections to information dissemination. However, the new technology development carried out by the Sang Nila Utama Museumis limited to making a one-way website and information system. Social media is a two-way platform that has great potential to be used to disseminate information about the Sang Nila UtamaMuseum directly to the public's smartphones. Community service activities carried out in the form of counseling on the use of chatbot applications that are integrated with Telegram. Counseling participants were provided with the provision to add chatbot databases through web-based applications and were guided touse Telegram chatbots as well as ways to carry out promotions for museum visitors so they could use the facilities which were expected to attract public interest in browsing available information. Based on the results of the usability testing questionnaire, all participants strongly agreed that the information contained in the application was organized, the application was easy to use and overall,the application supported the information dissemination process in the museum properly and optimally. Overall,the application works according to the functions that have been designed which is indicated by a high average value of 4.48. Partners feel very satisfied and recommend that similar service activities be carried out regularly